2013
DOI: 10.1155/2013/864747
|View full text |Cite
|
Sign up to set email alerts
|

UPLC Q-TOF/MS-Based Metabolic Profiling of Urine Reveals the Novel Antipyretic Mechanisms of Qingkailing Injection in a Rat Model of Yeast-Induced Pyrexia

Abstract: Fever is one of the most common clinical symptoms of many diseases. Qingkailing (QKL) injection is widely used in China as a clinical emergency medicine due to its good antipyretic effects. It is a herbal formula which is composed by eight kinds of traditional Chinese medicines (TCM). As a kind of typical multiple constituents and multiple actions of TCM, it is very difficult to elaborate the antipyretic mechanism by conventional pharmacological method. Metabonomics technique provides beneficial tool for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…These characteristics suggested a network with a small‐world property. This property demonstrated that alterations of a few important metabolites would trigger a more severe impact than changes occurring in marginal or relatively isolated positions (Gao et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics suggested a network with a small‐world property. This property demonstrated that alterations of a few important metabolites would trigger a more severe impact than changes occurring in marginal or relatively isolated positions (Gao et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The global, unbiased metabolic profiling platform was based on a Waters ACQUITY Ultra Performance Liquid Chromatography (UPLC) system coupled to a Xevo G2-Q-TOF/MS. This platform was described in detail in our previous publication [ 25 ]. In brief, 200 μ L of each serum sample was thawed on ice and extracted by methanol protein precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed algorithm was evaluated using the metabolomics data reported in [17]. To reveal the antipyretic mechanism of Qingkailing (QKL) injection in yeast-induced pyrexia rats, two groups of yeast-induced pyrexia rats were used.…”
Section: Sample Background and Preparationmentioning
confidence: 99%